Growing, innovating, convincing, approving: intellectual stimuli from Adam Smith - Giorgio Rampa (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
It is argued that, differently from a diffuse practice among modern economists, one needs reading more than the first couple of pages of the Wealth of Nations in order to fully appreciate Smiths contribution to the economics of exchange, innovation and economic evolution. In particular, by going back to the History of Astronomy, the First Formation of Languages and the Theory of Moral Sentiments, one finds that in Smiths opinion any kind of social order (languages, theories, social norms, evaluation of products) stems from a co-evolution process. Evolution is fostered by surprise and imagination, i.e. by dissatisfaction with some existing order; however imagination (that is, innovation) can only be successful if it is approved by the community; approval, in turn, is grounded on uses, customs, moods. As a consequence, there is no guarantee that evolution is progressive. More important, self-reference and the very mechanisms of imagination (from sudden surprise to sudden invention to successful new knowledge links) imply that evolution is characterised by highly non-linear relations. It follows that, as usual in non-linear theory, there does not exist a unique path of development for a society, nor one which depends uniquely on fundamental parameters. Some of Smiths key notions -like specialization, division of labour, effectual demand, propensity to exchange, self interest, prosperity- can be read from this different perspective, leading to an interpretation which is differs deeply from the one usually adopted by modern economics.
Keywords: O10; O31; D83; B31; 330